ANALISIS FLYPAPER EFFECT PADA BELANJA DAERAH PEMERINTAH INDONESIA - Dina Syahrina (2020)
The purpose of this study is to know the effect of the Local Own-source Revenue, the General Allocation Fund, the Special Allocation Fund, the Revenue Sharing Fund, and the Other Lawful Local Revenue towards the Regional Expenditures and also the analysis of The Flypaper Effect. The objects of this study are the regencies/cities in Indonesia. The sample used for this research are 472 samples of regencies/cities in Indonesia at 2018. The sampling technique used is Purposive Sampling methods with predetermined criteria. The data used for this research comes from the report of local government finances which published by the audit Board of the Republic of Indonesia. The Hypotesis testing of this study is analyzing the multiple linear regression by using SPSS version 20 with 5% significancy level. Partial result of this study is showing that the Local Own-source Revenue have positive effect on regional expenditure with a significance level of 0,000, the General Allocation Fund have positive effect on regional expenditure with a significance level of 0,000, the Special Allocation Fund have positive effect on regional expenditure with a significance level of 0,000, the Revenue Sharing Fund have positive effect on regional expenditure with a significance level of 0,000, the Other Lawful Local Revenue have positive effect on regional expenditure with a significance level of 0,000. Furthermore, the result of this study finds out the Flypaper Effect phenomenon on regional expenditure from the General Allocation Fund, whereas the phenomenon cannot be found at the Special Allocation Fund and the Revenue Sharing Fund.